Porfolios of Evidences for Contextualized Learning and Formative Assessment in Computer Engineering: Experiences in the Course of Algorithm Analysis - Munguía Molina, Diego (2021)
The course Analysis of Algorithms from the major in Computer Science at TEC is fundamental part of the academic preparation of professionals in the areas of software engineering or computer science. I also has a strong mathematical component that differentiates it from other courses that are more focused on programming. Based on these characteristics, three questions to improve the course were formulated: How can meaningful, permanent learning of contents be fostered?, How can these instances of learning be placed in a context that allows applying them for society’s improvement and well-being?, and How can a more fair and more formative assessment process be attained? Thus, a methodology of pedagogical mediation focused on portfolios is proposed. The effects of applying this methodology in the course during two semesters was analyzed qualitatively from observations and students’ reflexions. The findings point to an improvement in students’ grades and deepening in the contents studied thanks to the opportunity and motivation to inquire, learn by doing, and reflect on one’s own learning.